STRATEGI MAHASANTRI UNIA DALAM MEMBANGUN BRAND IMAGE DI TENGAH MASYARAKAT: STUDI KASUS DI DESA PRAGAAN LAOK - Bidayatul Aisyah; Fathorrahman (LP2M IAIN Sultan Amai Gorontalo, 2025)
ABSTRACT The development of education in the era of globalization has undergone significant changes as a direct result of advances in science and technology. In this situation, building a brand image is one of the important strategies that must be implemented by educational institutions to increase competitiveness and gain trust and legitimacy from the wider community. The strategy can be realized through a differentiation approach, which is creating unique values that distinguish an institution from other institutions. This study aims to examine the strategy of UNIA Prenduan Islamic Boarding School University Student in building a brand image in the community and identifying supporting and inhibiting factors that influence the implementation of the strategy. This research uses a qualitative approach with a case study type. Data collection techniques include in-depth interviews, participatory observation, and documentation, while data analysis is carried out using an interactive analysis model: data reduction, data presentation, and conclusion drawing and verification. The results showed that the Islamic Boarding School University Student strategy includes strengthening Islamic identity, using digital media as a means of da'wah, involvement in socio-religious activities, strengthening institutional networks, and exemplary in community life. Supporting factors include institutional support, community participation, internal enthusiasm, and program sustainability. The obstacles faced are limited resources, time management, and diverse community expectations. The findings are expected to be a strategic reference for educational institutions in shaping a strong, positive, and sustainable institutional image in the community.